Molecular and serological prevalence of Anaplasma marginale in water buffaloes in northern Brazil - Silva, Jenevaldo Barbosa da [UNESP]; Sousa Vinhote, Wagner Marcelo; Chaves Oliveira, Carlos Magno; Andre, Marcos Rogerio [UNESP]; Machado, Rosangela Zacarias [UNESP]; Fonseca, Adivaldo Henrique da; Barbosa, Jose Diomedes (Elsevier B.V., 2014)
Bovine anaplasmosis, caused by Anaplasma marginale, occurs in tropical and subtropical regions throughout the world and is a major constraint on cattle production in many countries. Approximately 60% of the buffalo herds in South America are located in northern Brazil. However, compared with the research on cattle, research on buffaloes has been neglected. Therefore, the present study was conducted to investigate the distribution of A. marginate in water buffaloes in northern Brazil. A total of 500 buffalo blood samples was randomly collected from 16 provinces and was analyzed using both nPCR assay and ELISA techniques. The percentage of animals that were seropositive for A. marginate according to ELISA was 49% (245/500). The main risk factors associated with seroprevalence were the region (p = 0.021; OR = 1.2) and the reproductive status (p =0.0001; OR = 1.6). Anaplasma marginate DNA was detected in 5.4% (27/500) of the sampled buffaloes. Our data provide information about the incidence of A. marginate infection in water buffaloes and may guide future programs aimed at controlling the disease in the northern region of Brazil. Although these water buffaloes are exposed to A. marginate, a low rate of A. marginate PCR-positive animals was found, which could be explained by the habitat in which the sampled animals live because they exhibited a low rate of attached ticks on their skin. (C) 2013 Elsevier GmbH. All rights reserved.
Keywords: anaplasmosis; Brazil; ELISA; PCR; Water buffaloes